Hepatitis B prevalence and associated factors in adults presenting for infection screening in northern Thailand - Nicolas Salvadori; Ludovic Gauthier; Marine Guy; Nicole Ngo-; Woottichai Khamduang; Luc Decker; Jullapong Achalapong; Jean Yves Mary; Wasna Sirirungsi; Sakorn Pornprasert; Surachet Arunothong; Sumet Ongwandee; et al. (Elsevier, 2023)
Background and aims: Hepatitis B is a leading cause of morbidity and mortality worldwide. In view of the World Health Organization 2030 targets, effective screening of chronic infection is crucial. We have assessed the prevalence and risk factors of hepatitis B surface antigen in adults presenting for screening. Methods: Free-of-charge and anonymous services for simultaneous hepatitis B, hepatitis C, human immunodeficiency virus and syphilis screening and counseling were provided in four facilities in northern Thailand. Analyses were performed separately in clients born before integration into the 1992 hepatitis B vaccine Thailand's Expanded Program on Immunization and in clients born afterwards. Results: Between October 2015 and August 2020, hepatitis B surface antigen prevalence was 7.2 % (185/2578) in clients born before 1992 (95 % confidence interval [CI] = 6.2%-8.2 %). In the multivariable analysis, characteristics independently associated with a higher risk of infection were being born male (adjusted odds ratio [aOR] = 1.49, 95 % CI = 1.10-2.01) and being part of a hill tribe (aOR = 1.65, 95 % CI = 1.01-2.70). Forty-two percent were unaware of their infection. In clients born in 1992 or afterwards, prevalence was 1.5 % (43/2933) (95 % CI = 1.1%-2.0 %) and characteristics independently associated with a higher risk were being born between 1992 and 1995 (aOR = 1.90, 95 % CI = 1.00-3.61), being born male (aOR = 2.60, 95 % CI = 1.34-5.07), being part of a hill tribe (aOR = 5.09, 95 % CI = 2.52-10.26) and having ever injected drugs (aOR = 4.33, 95 % CI = 1.23-15.24). Conclusions: Risk factor-based screening would miss many chronic hepatitis cases. Screening all adults once in their lifetime may be beneficial until the second generation of immunized infants have reached adult age.